Agribusiness Indicators : Nigeria - World Bank Group (World Bank, Washington, DC, 2015)
The purpose of this Agriculture Business Indicators Study was to isolate the success factors and construct indicators that reflect the performance of the agriculture sector in Nigeria and that benchmark it in terms directly comparable to agriculture sectors in other developing countries. Providing policy makers and public officials with access to this type of empirical information is seen as way to stimulate and inform policy dialogue about what reforms are needed and about how scarce public resources can be most effectively invested. The indicators can be used to identify specifically where this investment can be used to leverage commercialization through value addition, increasing the competitiveness of a country’s agricultural products domestically, regionally, and in international markets. They can also inform decision makers and investors about which policy measures are likely to be the most effective in enhancing food security, reducing poverty, and encouraging sustainable forms of environmental management. To accelerate agricultural development capable of spurring competitiveness of agricultural products in the domestic, regional, and international markets and could enhance food security; poverty reduction and sustainable environmental management. The study entailed a review of existing literature and the use of informal surveys to obtain information from a variety of stakeholders and actors. The focus was on the key success factors that the Agribusiness Indicators (ABI) team determined to be the most critical factors influencing agribusiness development in Sub-Saharan African countries. The Nigeria study was informed by the outcomes of scoping missions which had been conducted in three initial pilot countries: Ghana, Ethiopia and Mozambique.